"We have answered their prayer": American Jewish old age homes as guardians of religious tradition. Issue 2 (3rd July 2017) - Friedberg, Edna
ABSTRACT: The old age home was the major American Jewish communal response to aged poverty during the late nineteenth and early twentieth centuries. The first homes offered a self-conscious projection of their sponsors as socially progressive and compassionate in a new landscape. For a religious community increasingly distanced from formal hierarchies of traditional religious practice, the highly visible performance of good deeds under explicitly Jewish auspices became central to its communal identity. Acting on a combination of compassion and the perceived moral imperative of providing a Jewish environment, the founders and supporters of these homes recast Judaism and Jewish identity through an idealized image of aged piety.